Fiscal Rules and the Pro-Cycylicality of Public Investment in the West African Economic and Monetary Union - Dessus, Sébastien; Diaz Sanchez, Jose Luis; Varoudakis, Aristomene (World Bank, Washington, DC, 2013)
Evidence from a large panel of low-income and lower middle-income countries over the period 1995–2012 suggests that, contrary to other countries, public investment in the West African Economic and Monetary Union (WAEMU) has been pro-cyclical. Public investment contracts more in “bad times” than it increases in “good times” and appears to have become pro-cyclical since the introduction of the fiscal convergence criteria in 1994. The pro-cyclicality of public expenditure and the high asymmetry of shocks that affect WAEMU countries justify exploring options for greater counter-cyclicality of rules-based fiscal frameworks and for risk-sharing.